Use of electronic technologies in the University of the Philippines Diliman Libraries and its effects on users' information needs - Laxamana, Evelyn O. 1960- (2002)
This study was conducted to determine the following: (1) users needs and expectations in the use of electronic resources, (2) accessibility and availability of these resources to users, (3) obstacles faced in using these resources, and (4) users' degree of satisfaction in their use of the UP Diliman Library System Resources. Three hundred ninety five (395) library users were the respondents identified through purposive convenience random sampling. The data were gathered using a questionnaire patterned after Wenxiang Zhang (1998). Data gathered were organized, tabulated and analyzed using the Statistical Package for the Social Science (SPSS) software. The majority of the respondents are female (60 percent) undergraduate students (62 percent).
Results reveal that 32 percent of the respondents need more information materials and that access to these mateials at the UP Diliman Library system is moderately efficient. It was also revealed that users are more successful in finding materials contained in non-electronic resources or print materials. Seventy four (74 percent) prefer consulting periodical literature. In terms of electronic resources, the respondents prefer the Internet (72 percent) because it is deemed easily accessible. Secoond and third choices are the CD-ROM and OPAC. Other electronic resources such as the Proquest Academic Research Library (Online database), Britannica Online, other catalogs and databases are not familiar to library users. They use these electronic resources in the library except the Internet as the majority of the respondents access it at home. These formats are often utilized at 2-5 hours per week by (36 percent) of the respondents. The major obstacles that the respondents encountered in the use of electronic resources are not enough time or too busy to use the computer. Other obstacles discovered were lack of software (39 percent), lack of hardware (38 percent), lack of access to electronic resources (34 percent), and not enough training and assistance to operate the electronic resources (34 percent). Library users view the information provision services of the UP Diliman Library system as good (46 percent). Librarians and staff work performance were rated excellent (48 percent). Overall, the respondents are satisfied (65 percent) with the quality of information services provided by the UP Diliman Library System.
Library users needed and expected more in their use of electronic resources such as more mateials, better computer facilities, more library training in order to gain more knowledge in using electronic resources and to have more library tours, more staff assistance and more databases. In order to meet the above-mentioned needs and expectations, the study recommends the following: 1)Increase in the UP Diliman Library System's budget allocation; 2)full support from the University of the Philippines administrators specifically in the computerization of the UP Diliman Library system in order that the whole library system can provide access to a variety of electronic resources; 2)The UP Diliman Library System should continue conducting more library training, seminars and conferences specifically on the use of electronic resources to produce competent librarians and staff to deliver better or quality assistance to library users; 4) The UP Diliman Library system needs to integrate in their library orientation and tour basic knowledge in using the electronic resources available in the library and to advertise available electronic resources in order that library users be made aware of their existence; and 5) since the library is the preferred location for utilizing electronic resources, it is suggested that the UP Diliman Library system: a. Increase the one hour searching limit in the use of electronic resources; b. Increase the number of computers in the whole UP Diliman Library system in order to increase access to electronic resources; c. Enclose all computer printers or separate them from the reading areas or better still acquire Laserjet or Inkjet printers; d. Provide extended library hours; e. Reduce the fee in the use of the Internet because other students could not afford it; and f. Evaluate the different types of electronic resources in the UP Diliman Library system to prioritize which type should be acquired.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Keywords: Electronic information resources -- Use studies. -- Philippines -- Quezon City